2020
DOI: 10.3389/fonc.2020.534761
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated CD68+, CD163+, and MARCO+ Macrophages as Prognostic Biomarkers in Patients With Treatment-Naïve Gastroesophageal Adenocarcinoma

Abstract: Background: Despite improvements in surgical methodologies and perioperative chemo-and radiotherapy, the prognosis for patients with esophageal and gastric cancer remains poor. Hence, there is a great need to identify complementary biomarkers for improved treatment stratification. Tumor-infiltrating immune cells have been shown to impact on outcome in many types of cancer, including gastroesophageal cancer. The aim of this present study was to examine the prognostic value of tumor-infiltrating macrophages in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
4
23
0
2
Order By: Relevance
“…Tumor-infiltrating B cells are closely linked to the tumoral TLS and are considered to be actively involved in the immune response by directing T cell responses to antigens [34,35]. CD68 + TAMs, derived from the innate immune system, are associated with tumor progression and poor survival [36]. Furthermore, our findings showed that a high TLS signature was strongly associated with inflammation-related pathways and immune activation-related pathways.…”
Section: Discussionmentioning
confidence: 58%
“…Tumor-infiltrating B cells are closely linked to the tumoral TLS and are considered to be actively involved in the immune response by directing T cell responses to antigens [34,35]. CD68 + TAMs, derived from the innate immune system, are associated with tumor progression and poor survival [36]. Furthermore, our findings showed that a high TLS signature was strongly associated with inflammation-related pathways and immune activation-related pathways.…”
Section: Discussionmentioning
confidence: 58%
“…Only one study that assessed PET imaging with specific tracers for inflammation in a small group of vestibular schwannomas shown a higher cell density in non-growing tumors compared to growing VS [ 9 ]. The immunohistochemical markers CD68 and CD163 for the detection of tumor-associated macrophages are widely used [ 20 , 21 ]. However, the quantification of immunohistochemistry of macrophage markers is not standardized, and divergent results can be explained by technical limitations and antibody employment [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are also contrasting prognostic effects of the Foxp3/CD4 ratio in CGC and NCGC (25), which suggests that location may be an important factor for tumor progression. It is possible that neglecting the location during risk assessment could account for the differential findings in previous studies (26,27). Indeed, accumulating evidence has demonstrated distinct molecular a nd patho physi ologic al me chanisms of carcinogenesis in CGC and NCGC (28,29).…”
Section: Discussionmentioning
confidence: 95%